IMPLEMENTATION OF THE COOPERATIVE LEARNING TYPE TEAMMS GAMES TOURNAMET (TGT) MODEL WITH THE ASSISTANCE OF QUESTION CARDS TO IMPROVE STUDENT LEARNING OUTCOMES IN ELEMENTARY SCHOOL IPAS LEARNING - Kenari, - (2023)
This research is motivated by student problems in terms of social studies learning outcomes, so it requires teaching improvements by applying a cooperative learning approach to the Teams Games Tounmanet (TGT) type assisted by question cards. The aim of the research was to find out the increase in student learning outcomes after applying the Teams Games Tournament (TGT) type model with the help of question cards on social studies material in grade IV elementary school. This study used the Classroom Action Research (PTK) method with a spiral model research design by Kemmis and MC.Tanggart. The study used a sample of 17 students from class IVB SD 01 Nagrikaler. The research instrument, in the form of ability test questions to see an increase in student learning outcomes. Research data is presented in the form of pictures, tables, diagrams. The results showed that the use of cooperative learning type Teams Games Tournament (TGT) initial pre-test percentage of completeness was 17.65% or 3 students in the very poor category. In cycle II, student learning outcomes increased with an average student score of 80.58 or 88. .23% consisted of 15 students in the very good category. Based on the results of the study it was concluded that the use of the TGT model assisted by question cards was able to improve student learning outcomes